Assessing the Impact of Industrial Policies on Economic Development in Nepal - Kharel, Khom Raj (Economic Journal of Development Issues, 2016)
This study analyzes the impact of industrial policies on Nepalese economic development. For this, simple regression model has been applied to estimate the impact of industrial policies on macroeconomic growth. The impact of industrial policies is analyzed as pre-liberalization period (1974/75-1991/92), post liberalization period (1991/92-2009/10) and whole period (1974/75- 2009/10). The result shows that there are significant positive relationship between economic openness and industrial registration, GDP, industrial GDP, employment, investment, foreign trade (imports and exports), trade balance, total revenue and trade tax in the whole of 1974/75- 2009/10. During pre-liberalization period, these relationships have also been found positive, as well. But, during the post liberalization period, the impact of economic openness on the growth of industries, GDP, employment, investment, total revenue, trade tax, total trade, import trade, export trade and trade balance are not found positive. To achieve the satisfactory result the government policies should be appropriately reviewed to make them investment friendly and accelerate the industrial development in Nepal. Economic Journal of Development Issues Vol. 17 & 18 No. 1-2 (2014) Combined Issue, Page: 40-75